Perancangan Sistem Layanan Informasi Pariwisata Berbasis Mobile Internet Dengan Menerapkan Konsep Mobile Interaction - Octhario, Raymond; Syafei, Wahyul Amien Syafei Amien; Chritiyono, Yuli (Universitas Diponegoro, 2012)
Mobile interaction is about the stuff of people’s lives, focused on understanding and developing blueprints for systems that permeate the broad spectrum of their experiences. People can use system, They can take advantage of the system through mobile devices. Due to limitations in the display and display media such as mobile phones in presenting and giving information to the public. the design of interaction between the system and users will be very important, It is a thing to be considered to create a mobile internet-based information systems. Therefore, the application of mobile interaction design, especially in terms of mobile internet-based system is needed, so the system can be used optimally. Indonesia's tourism sector is one sector of the service economy. It has bright prospects for mobile interaction. However to enhance the role of development in Indonesia, is still one of many shortcomings that limited mediainformation services. This study concerns in produce and information service system especially in tourism of Palangka Raya whichapply the concept of mobile interaction design. To apply the concept of mobile interaction, there are three main activities. There areunderstanding users, developing prototype designs and evaluation. Percentage points is higher in the evaluation, indicates that the user is able to use the system and interact with the system and based on feedback from users, no complaints are ejected from the user in the system path. This provides an assessment of the success of the system design, system success and user satisfaction convey information to the system. Expected in the long periode, the system can increase tourism sector in the city of Palangka Raya.Keywords : Internet; Mobile Phones; Information Services; Mobile Interaction Design; Tourism